Maternal ochratoxin A exposure impairs meiosis progression and primordial follicle formation of F1 offspring. (October 2022) - Song, Yue; Zhao, Jinxin; Qiao, Tian; Li, Lan; Shi, Dachuan; Sun, Yonghong; Shen, Wei; Sun, Xiaofeng
Abstract: Ochratoxin A (OTA), a mycotoxin produced by Aspergillus and Penicillium fungi, widely contaminates feed, food and their raw materials. OTA has been proved to have hepatotoxicity and nephrotoxicity. Its reproductive toxicity needs to be further explored. We found that OTA inhibited the progression of meiosis, keeping more germ cells at leptotene and zygotene. Furthermore, OTA impaired primordial follicle formation, keeping more germ cells in cysts. Increased γH2AX suggested that DNA damage occurred both at the stages of meiosis and primordial follicle formation. The expression of RAD51 increased with the concentration of OTA at the stage of meiosis, while decreased later, suggesting the activated DNA repair induced by DNA damage then inhibited by persistent and excessive stress of DNA damage, which further induced apoptosis. DEGs caused by OTA were also mainly enriched in DNA damage and repair through RNA-seq analysis. Higher level of reactive oxygen species (ROS) and increased degree of oxidative damage marker 8-OHdG were both found in the ovaries exposed to OTA. We concluded that maternal OTA exposure affected meiosis progression and primordial follicle formation via oxidative damage and DNA repair. Clarification of the mechanism of OTA will contribute to the development of more effective detoxification strategies. Graphical abstract: Image 1 Highlights: Maternal OTA exposure inhibits the progression of meiosis prophase I. Maternal OTA exposure leads to abnormality of o primordial follicle formation. Maternal OTA exposure diminishes ovarian reserve. OTA-induced reproductive toxicity comes from the imbalance of DNA damage and repair.